Mycobacterium tuberculosis Modulates miR-106b-5p to Control Cathepsin S Expression Resulting in Higher Pathogen Survival and Poor T-Cell Activation - Pires, David; Bernard, Elliott M.; Pombo, João Palma; Carmo, Nuno; Fialho, Catarina; Gutierrez, Maximiliano Gabriel; Bettencourt, Paulo; Anes, Elsa (Frontiers in Immunology, 2017)
The success of tuberculosis (TB) bacillus, M. tuberculosis (Mtb), relies on the ability to survive in host cells and escape to immune surveillance and activation. We recently demonstrated that Mtb manipulation of host lysosomal cathepsins in macrophages leads to decreased enzymatic activity and pathogen survival. In addition, while searching for microRNAs involved in post-transcriptional gene regulation during mycobacteria infection of human macrophages, we found that selected microRNAs such as miR-106b-5p were specifically up-regulated by pathogenic mycobacteria. Here, we show that miR-106b-5p is actively manipulated by Mtb to ensure its survival in macrophages. Using an in silico prediction approach, we identified miR-106b-5p with a potential binding to the 3'-untranslated region (3'-UTR) of cathepsin S (CtsS) mRNA. We demonstrated by luminescence-based methods that miR-106b-5p indeed targets CTSS mRNA resulting in protein translation silencing. Moreover, miR-106b-5p gain-of-function experiments lead to a decreased CtsS expression favoring Mtb intracellular survival. By contrast, a miR-106b-5p loss-of-function in infected cells was concomitant with increased CtsS expression, with significant intracellular killing of Mtb and T-cell activation. Modulation of miR-106b-5p did not impact necrosis, apoptosis or autophagy arguing that miR-106b-5p directly targeted CtsS expression as a way for Mtb to avoid exposure to degradative enzymes in the endocytic pathway. Altogether, our data suggest that manipulation of miR-106b-5p as a potential target for host-directed therapy for Mtb infection.